INVESTIGATING THE INFLUENCE OF STRAW CONTENT AND LOADING DEGREE OF THE THRESHER OF ACROS-530 AND “JD-9500” COMBINE HARVESTERS ON THE QUALITY OF THRESHING WINTER WHEAT GRAIN - Burlaka, O. A.; Yakhin, S. V.; Drozhchana, O. U. (Scientific Progress & Innovations, 2019)
The purpose of this article is to determine the influence of grain mass strawiness and loading level of the thresher of the ACROS-530 and “JD-9500” combine harvesters conducted according to the classical tangential scheme of grain threshing on the quality of separation – grain losses behind the combine harvester and impurities content of bin grain under the direct harvesting of winter wheat in agro-climatic conditions of Poltava district, Poltava region Based on the analysis of the experimental data response surfaces were constructed, characterizing the dependence between the height of plants’ cutting X1, cm; bin grain impurities content Y1, %; and grain losses, Z1, % (harvesting winter wheat by ACROS-530 and “JD-9500” combines harvesters with the speed of 4.5 km/h). It should be mentioned that for agro-technical conditions of Poltava district, the optimal cutting height varies within 5 ... 15 cm at direct harvesting of winter wheat grain and the yield up to 5 t/ha. At the same time, smaller height of cutting is recommended by agro-technical conditions for manufacturing crop growing products, and increasing the height of cutting improves the effectiveness of operating the separating mechanisms of combine harvesters. Therefore, if it is necessary to pick almost all straw, it is recommended to reduce the speed of basic combine harvester’s equipment. If part of straw is left in the field as organic fertilizers, the criteria of harvester loading are losses behind threshing unit and the content of grain impurities transported in the bin. Analyzing the experimental data, the dependences between the speed of ACROS-530 and “JD-9500” combine harvesters – X1ʹ, km/h, the content of bin grain impurities Y1, %, and grain losses Z1, % at the fixed height of cutting – 7…10 cm, were revealed; it was established that the best indicators of grain threshing quality were received at traveling speed 4.5... 5 km/h But under the identical capacity of combine harvesters per unit of the threshing set width, grain losses on the “JD- 9500” combine harvester (0.5…1 %) and the content of bin grain impurities (2…3.5 %) were less in comparison with the ACROS-530 at other invariable harvesting conditions. It is stipulated by more perfect design of air-screen cleaning of the “JD-9500” harvester. It is expedient to use the obtained research results as recommendations in the work of engineering and agronomic departments when carrying out quality control and technological equipping combine harvesters, designed according to the classical scheme of the threshingseparating device, while threshing winter wheat at agricultural enterprises and on farms of Poltava district, Poltava region.